Low insulin-like growth factor-1 levels are associated with anaemia in adult non-diabetic subjects - Succurro, Elena; Arturi, Franco; Caruso, Vittoria; Rudi, Stefania; Sciacqua, Angela; Andreozzi, Francesco; Hribal, Marta L.; Perticone, Francesco; Sesti, Giorgio (Thrombosis and Haemostasis, 2011)
Anaemia is a risk factor for cardiovascular morbidity and mortality. Among factors responsible for anaemia, insulin-like growth factor-1 (IGF-1) is a plausible candidate. We evaluated the association of IGF-1 with haemoglobin (Hb) concentration and anaemia in a cohort of 1,039 Caucasians subjects. Subjects with anaemia exhibited lower IGF-1 (p=0.006), and higher hsCRP levels (p=0.003). To estimate the independent contribution of variables to Hb concentration, a multivariable regression analysis was modeled including age, gender, body mass index (BMI), waist circumference, blood pressure, fasting glucose, fasting insulin, IGF-1, fibrinogen, hsCRP, mean corpuscular haemoglobin (MCH), mean corpuscular volume (MCV), serum iron, estimated glomerular filtration rate (eGFR), and treatment with angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs). The variables significantly associated with Hb concentration were gender (p<0.0001), IGF-1 (p<0.0001), waist circumference (p=0.02), hsCRP (p<0.04), MCH (p<0.0001), MCV (p<0.0001), serum iron (p=0.001), IGF-1 (p=0.003), hsCRP (p=0.008), and waist circumference (p=0.01), accounting for 54.0% of its variation. Hb concentration was significant lower in subjects in the lowest IGF-1 quartile as compared with those in the third (p=0.02) and fourth (p=0.001). In a logistic regression model adjusted for age, gender, BMI, waist circumference, blood pressure, fasting glucose, fasting insulin, fibrinogen, hsCRP, MCH, MCV, serum iron, eGFR, and treatment with ACE inhibitors or ARBs, subjects in the first quartile of IGF-1 had a 2.49-fold higher risk of having anaemia as compared with those in the fourth (odds ratio 2.70, 95% confidence interval 1.02–7.16). Our data suggest that low IGF-1 may be an important contributor to mild anaemia.
Keywords: Anaemia; IGF-1; cardiovascular risk; inflammation